2020
DOI: 10.1080/02791072.2020.1769878
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Placebo-Controlled Trials of Psychedelic-Assisted Therapy

Abstract: After a two-decade hiatus in which research on psychedelics was essentially halted, placebo-controlled clinical trials of psychedelic-assisted therapy for mental health conditions have begun to be published. We identified nine randomized, placebo-controlled clinical trials of psychedelic-assisted therapy published since 1994. Studies examined psilocybin, LSD (lysergic acid diethylamide), ayahuasca (which contains a combination of N,N-dimethyltryptamine and harmala monoamine oxidase inhibitor alkaloids), and MD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 44 publications
(34 reference statements)
1
71
0
1
Order By: Relevance
“…While psychedelic use has thrived for thousands of years in Indigenous cultures and for many decades in underground subcultures, psychedelics are increasingly being encountered in the mainstream in countries around the world, as evidenced by a surge of media attention on the therapeutic use of psychedelics, including popular books written on the topic [ 1 ]. The potential application of psychedelics in combination with therapy for the treatment of mental health difficulties has been studied in at least 10 published placebo-controlled, randomized trials to date, with early results appearing promising [ 2 ]. As a result of these and other events, many individuals suffering from mental health issues are now seeking to utilize psychedelics for healing, especially in cases where currently available psychotherapeutic or psychopharmacological treatments have failed.…”
Section: Background Information On Psychedelic Therapy Harm Reductiomentioning
confidence: 99%
See 1 more Smart Citation
“…While psychedelic use has thrived for thousands of years in Indigenous cultures and for many decades in underground subcultures, psychedelics are increasingly being encountered in the mainstream in countries around the world, as evidenced by a surge of media attention on the therapeutic use of psychedelics, including popular books written on the topic [ 1 ]. The potential application of psychedelics in combination with therapy for the treatment of mental health difficulties has been studied in at least 10 published placebo-controlled, randomized trials to date, with early results appearing promising [ 2 ]. As a result of these and other events, many individuals suffering from mental health issues are now seeking to utilize psychedelics for healing, especially in cases where currently available psychotherapeutic or psychopharmacological treatments have failed.…”
Section: Background Information On Psychedelic Therapy Harm Reductiomentioning
confidence: 99%
“…However, advocates such as the Multidisciplinary Association for Psychedelic Studies (MAPS) persisted in efforts to obtain legal permission to conduct psychedelic research and there has been a recent resurgence of well-controlled clinical trials providing strong preliminary evidence for the use of some psychedelics for therapeutic purposes. A recent meta-analysis of nine rigorous placebo-controlled trials of psychedelic-assisted therapy was conducted and found a “very large” between-groups effect size of 1.21 (Hedges g ) which is notably larger than average effect sizes for standard treatments using psychotherapy or psychopharmacological medications [ 2 ]. While previous decades of psychedelic research have focused on a wide array of psychological problems using many different psychedelic substances, modern research has demonstrated the strongest evidence for psychedelic-assisted therapy in the treatment of post-traumatic stress disorder (PTSD) [ 18 ], depression [ 19 ], end-of-life distress [ 20 ], addiction [ 21 23 ], and social anxiety in adults with autism [ 24 ].…”
Section: Background and History Of Psychedelic Use And Scientific Resmentioning
confidence: 99%
“…Over the last decade there has been a growing interest in psychedelic-assisted psychotherapy for the treatment of a variety of mental health conditions such as anxiety, depression, substance abuse, OCD, and posttraumatic stress disorder (PTSD; Luoma et al, 2020). Psychedelic-assisted psychotherapy refers to pairing psychedelic substances with psychotherapeutic interventions to maximize therapeutic outcomes.…”
Section: Introduction To Psychedelic-assisted Therapiesmentioning
confidence: 99%
“…Psychedelic therapy offers several advantages over conventional anti-depressant treatment. Most notably, psychedelic therapy appears to produce greater reductions in depression symptoms when compared to typical pharmacological and psychological treatments (24). These symptom changes typically result from a short treatment program and usually occur immediately following treatment, unlike the weeks or months typically seen in current treatments (25).…”
Section: Classic Psychedelics and Depressionmentioning
confidence: 99%